2022
DOI: 10.1155/2022/5910019
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usage of Different Doses of Cis-Atracurium in Intracranial Aneurysm Surgery and Its Effect on Motor-Evoked Potentials

Abstract: The objective of this work was to investigate the effect of different doses of cis-atracurium on patients undergoing general anesthesia induction (GAI) during intracranial aneurysm surgery (ICAS). In this work, 90 patients who underwent ICAS under the elective motor-evoked potential (MEP) monitoring in the First Affiliated Hospital of Northwest University (Xi’an No. 1 Hospital) from January 2021 to May 2022 were enrolled as the research objects. Randomly, they were rolled into a S1 group (30 cases, 2 times 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…At the T3 time point, we found that the hemodynamic changes in the ROC1 group were greater than those in the other two groups, but the difference was not statistically significant, which is consistent with the results of previous studies ( 29 , 30 ). In the ROC1 group, the number of patients with intraoperative body movement increased significantly.…”
Section: Discussionsupporting
confidence: 91%
“…At the T3 time point, we found that the hemodynamic changes in the ROC1 group were greater than those in the other two groups, but the difference was not statistically significant, which is consistent with the results of previous studies ( 29 , 30 ). In the ROC1 group, the number of patients with intraoperative body movement increased significantly.…”
Section: Discussionsupporting
confidence: 91%